STRATEGIC ORIENTATION AND HUMAN RESOURCE PRACTICES IN SERVICE INDUSTRY - Anita Mathew (Abhigyan, 2010)
Strategic Human Resource Management aims to achieve congruence between HRM practice and strategy. It is also argued that given unique characteristics of the service firms, they should develop a more strategic HRM orientation. In spite of the relatively widespread acceptance of the theory there is very little evidence of its existence in practice. This study undertakes an empirical examination of the relationship between HRM practice and strategy in the service sector in some of the service firms. The findings show that there are external influences and contingencies other than strategy that exert a greater influence on HRM practice.